2021
DOI: 10.3390/app112210587
|View full text |Cite
|
Sign up to set email alerts
|

Employer’s Information Requirements: A Case Study Implementation of BIM on the Example of Selected Construction Projects in Poland

Abstract: Case studies available in the literature clearly point to the numerous benefits of BIM (Building Information Modeling), in addition to the barriers that participants of such projects may face. This paper is a case study of Employer’s Information Requirements (EIR) for preparing and managing BIM models in the design and construction of selected large public construction projects: the Cogiteon Lesser Poland Science Center (LPSC Cogiteon), the Krakow Music Center (KMC) and the Copernican Revolution Studio (CRS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…2) ICT Skills: Turk [32] defined ICT skills as the knowledge that allows communities to participate within a networked society. Computer or ICT literacy is the skills students require to operate various computer applications, such as word processing, databases, and spreadsheets [33]. Furthermore, there are Information Technology (IT) skills such as copying disks and generating hard copy printouts [32].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2) ICT Skills: Turk [32] defined ICT skills as the knowledge that allows communities to participate within a networked society. Computer or ICT literacy is the skills students require to operate various computer applications, such as word processing, databases, and spreadsheets [33]. Furthermore, there are Information Technology (IT) skills such as copying disks and generating hard copy printouts [32].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, there are Information Technology (IT) skills such as copying disks and generating hard copy printouts [32]. It is the skills to know how to use a computer and relevant software [30], [33], [34].…”
Section: Methodsmentioning
confidence: 99%
“…Public procurement, however, above all, should be competitive, therefore the BIM mandatory should be preceded by preparation of the industry, in the understanding of companies that are potential bidders of the tender. The investor's information requirements should be an important document that, when properly written, helps to avoid disappointment with the product received [26], and is also adapted to the contractors' capabilities. Due to looking at the whole life cycle of built asset, it is complicated and it is worth approaching its development meticulously.…”
Section: Discussionmentioning
confidence: 99%
“…A survey conducted with owners in North America on BIM adoption and its value found that better definition of BIM deliverables among stakeholders is a key factor in increasing the benefits of its use [ 28 ]. In this context, Zima & Mitera-Kiełbasa [ 29 ] presented a case study on the preparation and management of BIM models in the design and construction of three large public sector projects in Poland. It addressed the three areas that constitute Exchange Information Requirements (EIR): technical, management and strategic.…”
Section: Literature Reviewmentioning
confidence: 99%